Endoscopic resection of a duodenal duplication cyst: A case report - Sayumi Kurita; Kazuo Kitagawa; Naoki Toya; Masahiko Kawamura; Muneo Kawamura; Ken Eto (DEN Open, 2022)
Abstract A duodenal duplication cyst (DDC) is a rare congenital anomaly. Gastrointestinal duplication cysts are traditionally treated by complete surgical resection due to the potential precancerous conditions. Here, we describe an asymptomatic DDC that was successfully treated using endoscopic resection. A submucosal tumor in the descending portion of the duodenum was detected in a 71‐year‐old female during a regular checkup at our hospital. Upper gastrointestinal endoscopy showed a 10‐mm pedunculated submucosal tumor. Endoscopic ultrasonography revealed a 10‐mm cystic tumor of low echogenicity that included nodules and debris. Endoscopic resection with hot snare polypectomy was performed for diagnosis and treatment. The postoperative course was uneventful. Histologic examination revealed that the cystic tumor was a DDC. Endoscopic resection is a safe, effective, and minimally invasive alternative to surgical resection for small DDCs with malignant potential.